Logistics Centre Location Selection Based on Logistics Costs: An Application in Isparta - Öçal, Bora (Current Studies in Social Sciences VI, 2023)
The aim of this study is to select a logistics centre location in Isparta province within the borders of Turkey based on logistics costs. Analytical Hierarchy Process (AHP) method and TOPSIS method were used in the study. Firstly, 5 logistics costs that are thought to affect the logistics centre location selection were determined and the importance levels of logistics costs were calculated by AHP method. Afterwards, 3 possible logistics centre locations in Isparta province were determined and the most suitable logistics centre location was calculated by TOPSIS method. As a result of the study, it was determined that the most suitable logistics centre location in Isparta is Keçiborlu district.